PERAN PENYULUH PERTANIAN DALAM MENINGKATKAN PENDAPATAN PETANI KELAPA DI KECAMATAN NUHON KABUPATEN BANGGAI - Puspapratiwi, Dian; Gandalia, Gabriel; Zaenuddin, Ruslan A.; Enteding, Trianto (Agros Journal of Agriculture Science, 2024)
Coconut plant is a commodity that has high economic value if managed properly, because it provides life to farmers. This study aims to determine the role of agricultural extension workers in increasing the income of Coconut farmers in Nuhon District. This research was conducted from August to November 2023, using quantitative descriptive analysis, namely the Likert analysis approach and income analysis. The results obtained are the role of extension agents on coconut farming income in Nuhon District, Banggai Regency as a mentor who conducts education has a high category (65.3%), then as a monitor and evaluator obtained in the medium category (50.6%), facilitating farmers obtained in the medium category (56%), and providing direction to farmers obtained in the medium category (56.6%), Thus the role of extension agents is still not optimal because agricultural extension agents are less active in playing a role for coconut farmers and for the results of the analysis of the income of coconut farmers obtained profitable results and feasible to develop in Nuhon District, Banggai Regency.